FAKTOR-FAKTOR YANG MEMPENGARUHI PEMBENTUKAN DAERAH BARU (Studi Kelayakan Secara Administratif Kabupaten Indragiri Selatan) - Puspitasari, Ratty; ", Sujianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The extent of government territory Indragiri Hilir in scalability problems of localgovernment into its own in terms of equity of service to the community. Government activitiesare concentrated in a particular region tends to make access to services neglected in certain areas,and even tend to be injustice in terms of development of infrastructure, both physical andcommunity education. Indragiri Selatan feasibility area administratively constrained in differentnames and area coverage of candidates Regency / City based Decision Regent Indragiri Hilir No.177 / IV / HK-2010 with Council Decision No. Indragiri Hilir 26 / Parliament / 2008 and No. 33/ Parliament / 2008.Theoretical concepts used in this research is the development of administrative theory byTjokrowinoto, the indicators are formulated in the theory of functions of planning,implementation and monitoring. Key informants in this study is the Indragiri Hilir RegencySecretary, Assistant Secretary Governance Indragiri Hilir Regency, Head of Regional AutonomySub Part, the Islamic University Academics Indragiri, Observers, Non-governmentalOrganizations, Community Leaders. This research is a qualitative descriptive study.The research concludes that the process of formation of the South Indragiri administrativedistrict in the unfavorable category. This is evidenced inconsistency in the interpretation ofGovernment Regulation No. 78 of 2007 related responses between people's aspirations Decree ofDistrict / City with a decree Indragiri Hilir which indicates lack of a common vision of the planto form the South Indragiri. This has led to the completion of the process of the formation of thedistrict administrative requirements Southern Indragiri takes much longer than it should. Onesuggested in this study is a unified vision between the parties concerned so that coordination canrun well.Keywords : Formation, Feasibility, Administrative